Obligatory features of Lithuanian verbal inflection classes - Pakerys, Jurgis (Vilnius University Open Series, 2021)
Lithuanian verbal inflection classes are defined by tense suffixes, stem‑forming affixes, vowel and consonant alternations, and accentuation patterns. I make a distinction between obligatory features that are relevant for every verb and non‑obligatory features that characterize only part of the verbs. I argue that the obligatory features are the present and the past tense suffixes combined with mobile and immobile accentuation patterns, while the rest of the features are optional. When only the obligatory features are taken into account, three types of the present tense (‑a‑, ‑i‑, ‑o‑) and two types of the past tense (‑ė‑, ‑o‑) suffixes are found in five combinations (‑a‑/‑ė‑, ‑a‑/‑o‑, ‑i‑/‑o‑, ‑o‑/‑ė‑, ‑o‑/‑o‑) with further variants defined by two types of mobile and one type of immobile accentuation, resulting in eighteen suffixal‑accentual combinations in standard Lithuanian. The combinations of features characterizing the present and the past stems support the view of inflection classes as classes of stems rather than of lexemes (Stump 2016).